Galactic bulges: the importance of early formation scenarios vs. secular evolution. Issue Volume 10:Issue S309(2014) (9th February 2015) - Seidel, Marja K.; Cacho, R.; Ruiz-Lara, T.; Falcón-Barroso, J.; Pérez, I.; Sánchez-Blázquez, P.; Vogt, F. P. A.; Ness, M.; Freeman, K.; Aniyan, S.
Abstract: We study the stellar content of three galactic bulges with the high resolution gratings (R=7000) of the WiFeS integral field unit in order to better understand their formation and evolution. In all cases we find that at least 50% of the stellar mass already existed 12 Gyrs ago, more than currently predicted by simulations. A younger component (age between ∼1 to ∼8 Gyrs) is also prominent and its present day distribution seems to be much more affected by morphological structures, especially bars, than the older one. This in-depth analysis supports the notion of increasing complexity in bulges which cannot be achieved by mergers alone, but requires a non-negligible contribution from secular evolution.